Safety and efficacy of saxagliptin for glycemic control in non-critically ill hospitalized patients. Issue 1 (29th March 2017) - Garg, Rajesh; Schuman, Brooke; Hurwitz, Shelley; Metzger, Cheyenne; Bhandari, Shreya
Abstract : Objective: To evaluate whether saxagliptin is non-inferior to basal-bolus insulin therapy for glycemic control in patients with controlled type 2 diabetes mellitus (T2DM) admitted to hospital with non-critical illnesses. Research design and methods: This was an open-label, randomized controlled clinical trial. Patients received either saxagliptin or basal-bolus insulin, both with correctional insulin doses. The main study outcome was the mean daily blood glucose (BG) after the first day of randomization. Results: Of 66 patients completing the study, 33 (age 69±10 years, 40% men) were randomized to saxagliptin and 33 (age 67±10 years, 52% men) to basal-bolus insulin therapy. The mean daily BG was 149.8±22.0 mg/dL in the saxagliptin group and 146.9±30.5 mg/dL in the insulin group (p=0.59). With an observed group difference of 2.9 mg/dL and an a priori margin of 20 mg/dL, inferiority of saxagliptin was rejected in favor of non-inferiority (p=0.007). There was no significant difference in the percentage of high or low BG values. The insulin group received a higher number of insulin injections (2.3±1.7/day vs 1.2±1.9/day; p<0.001) as well as a higher daily insulin dose (13.3±12.9 units/day vs 2.4±3.3 units/day; p<0.001) than did the saxagliptin group. Continuous BG monitoring showed that glycemic variability was lower in the saxagliptin group as compared to the insulin group. Patient satisfaction scores were similar in the two groups. Conclusions: We conclude that saxagliptin use is non-inferior to basal-bolus insulin in non-critically ill hospitalized patients with T2DM controlled on 0–2 oral agents without insulin. Saxagliptin use may decrease glycemic variability in these patients. Trial registration number: NCT02182895.